Assessment of functional elements of public finance management - A. Z. Namitulina; I. V. Soklakova; E. Yu. Kuzmina; E. A. Buryak (Вестник университета, 2020)
The article assesses the main functional elements of public Finance management: planning, operational management and control. Financial planning and forecasting presently depend not only on macroeconomic and microeconomic factors, but also on geopolitical factors. Economic sanctions, which are still ongoing, have a particular impact, so it is impossible to make an accurate forecast in the management of public finances. Operational public financial management can never be considered without public resources designed to support and implement the activities of all areas of the country’s life. The paper pays special attention to the control function due to the lack of a single objective control system. To improve efficiency, the authors propose to use certain criteria: the performance criterion and the criterion of inappropriate use of budget funds. The paper calculates the dependence of Federal budget revenues on the level of gross domestic product (GDP) and the level of unemployment. The authors use for the calculation a standard form of regression equation that takes into account statistical correlations. The results of this study can be used to improve the efficiency of Federal budget revenue planning.